2022
DOI: 10.3390/ma15030861
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of Room Temperature Superelasticity in Ti-Mo-Al Alloy System via Manipulation of ω Phase Stability

Abstract: The achievement of room-temperature (RT) superelasticity in a Ti-Mo-Al ternary alloy system through the addition of a relatively high concentration of Al to manipulate the phase stability of the ω phase is realized in this study. The composition of the Ti-6 mol% Mo (Ti-11.34 mass% Mo) alloy was designated as the starting alloy, while 5 mol% Al (=2.71 mass% Al) and 10 mol% Al (=5.54 mass% Al) were introduced to promote their superelastic behavior. Among the alloys, Ti-6 mol% Mo-10 mol% Al alloy, which was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Along with the phase identification results from Figure 2 , it could thus be determined that the alloys (b) Ti–Al–Cr, (c) Ti–Al–Co, and (d) Ti–Al–Ni were composed of the single parent β phase. Additionally, these microstructures are similar to that of the Ti–Al–Mo alloy in our previous result [ 25 ], which is cited in Figure 3 e for comparison. On the other hand, in Figure 3 a, obvious precipitates, which are pointed out by arrows, can be observed.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Along with the phase identification results from Figure 2 , it could thus be determined that the alloys (b) Ti–Al–Cr, (c) Ti–Al–Co, and (d) Ti–Al–Ni were composed of the single parent β phase. Additionally, these microstructures are similar to that of the Ti–Al–Mo alloy in our previous result [ 25 ], which is cited in Figure 3 e for comparison. On the other hand, in Figure 3 a, obvious precipitates, which are pointed out by arrows, can be observed.…”
Section: Resultssupporting
confidence: 86%
“…In the continuous tensile tests, it was found that no obvious two-stage yielding behavior could be found in the Ti–Al–X (X = (a) Cr, (b) Co, and (c) Ni) alloys. On the other hand, it was found that the Ti–Al–Mo [ 25 ] alloy shows slight two-stage yielding in the literature. The first-stage yielding indicates the stress-induced martensite transformation (SIMT), while the second yielding suggests the plastic deformation (i.e., slip of dislocations).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations